(untitled) (Research, Society and Development, 2021)
Water is one of the resources widely used in agriculture, and this is responsible for the consumption of more than 72% of all the water used in the country, it is valid to notice that over time the water crises were getting worse and regions such as the Northeast were quite affected by drought, so it has become increasingly imperative the need for new methods to reduce water waste. Regarding it, this article has as its main purpose to emphasize the importance of Water Footprint, following studies of revisions to the northeastern farming, this article presents the Water Footprint as one of the solutions for the reduction of waste of domestic water, industrial and agricultural sector, in order to reduce future impacts caused by lack of water. Therefore, it is essential to the use of new techniques linked to better to utilization of water for upgrade in agricultural production.